Applying geoprocessing resources in the declivity analysis of the cycling network of the city of São Paulo - Simeão, João Vitor Penteado [UNESP]; Manzato, Gustavo Garcia [UNESP]; Viviani, Eliane (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2019)
The huge fleet of vehicles causes environmental impacts, congestion and affects urban mobility and the quality of life of the population. In this context, sustainable urban mobility suggests the use of non-motorized modes as a way to change this reality. Bicycles are an example: they are versatile and non-polluting. The incentive for its use focuses on governmental measures, which include the provision of infrastructure and adequate physical conditions, such as declivity. Several technical guides indicate that slopes above 5% should be avoided because they are difficult for cyclists on the way up and can lead to high speeds in descending ways. In order to investigate the real condition of a cycling network in terms of its declivity, the cycling network of the city of São Paulo was studied. Using geoprocessing resources, two strategies were applied: the first one focused on the intersection of the cycling network vector database and a declivity map; and the second one on the generation of a digital elevation model using contour lines and subsequent assignment of altimetric information to the cycling network. The results obtained with the first strategy indicated 47% of the São Paulo’s cycling network comprises links whose slopes are above 5%. On the other hand, the analyses with the contour lines revealed that 17,9% of the cycling network has slopes above 5%. The concluded was that the most part of the cycling network is composed by routes with adequate declivities, which should not result in major difficulties for cyclists.
Recursos de Geoprocessamento Aplicados à Análise da Declividade da Malha Cicloviária da Cidade de São Paulo
Keywords: Cycling infrastructure; Digital elevation model; Sustainable urban mobility